Regularity and Stochasticity of Nonlinear Dynamical Systems (Nonlinear Systems and Complexity,, 2018)
This book presents recent developments in nonlinear dynamics and physics with an emphasis on complex systems. The contributors provide recent theoretic developments and new techniques to solve nonlinear dynamical systems and help readers understand complexity, stochasticity, and regularity in nonlinear dynamical systems. This book covers integro-differential equation solvability, Poincare recurrences in ergodic systems, orientable horseshoe structure, analytical routes of periodic motions to chaos, grazing on impulsive differential equations, from chaos to order in coupled oscillators, and differential-invariant solutions for automorphic systems, inequality under uncertainty. Presents the most up-to-date understanding in nonlinear dynamical systems along with new theories and methodologies applied to nonlinear physics, engineering, and social science; Includes differential-invariant solutions, classification of orientable horseshoes, and nonlinear time-delay systems; Illustrates solution routes to chaos for nonlinear differential equations.